PERKEMBANGAN CABANG OLAHRAGA SURFING SEBAGAI SALAH SATU SPORT TOURISM DI KAWASAN PANTAI SENGGIGI KABUPATEN LOMBOK BARAT - Jaelani, Ahmad; Elya Wibawa Syarifoeddin; Fitri Anggraeni (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This study analyzed the development of surfing as a sport tourism attraction in the Senggigi Beach area, West Lombok Regency. The study used a descriptive quantitative design with questionnaire-based data collection. Respondents consisted of 40 stakeholders, including local surfing athletes, surfing organization administrators, MSME actors, outdoor-equipment rental providers, and villa owners around Senggigi Beach. Data were analyzed descriptively using percentages. The findings show that accessibility to the location (80%) and the presence of local MSMEs (70%) were the strongest supporting factors for surfing-based sport tourism development. Meanwhile, tourism infrastructure management (60%) and the availability of surfing training (55%) were rated as moderate, whereas cooperation with government stakeholders (45%) emerged as the weakest aspect. These results indicate that Senggigi has promising potential to strengthen surfing as a sport tourism product, but better governance, supporting facilities, and coordinated stakeholder collaboration are still needed to support sustainable destination development. Keywords: surfing, sport tourism, Senggigi Beach, West Lombok, destination development Penelitian ini bertujuan menganalisis perkembangan cabang olahraga surfing sebagai daya tarik sport tourism di kawasan Pantai Senggigi, Kabupaten Lombok Barat. Penelitian menggunakan desain kuantitatif deskriptif dengan pengumpulan data melalui kuesioner. Responden penelitian berjumlah 40 orang yang terdiri atas atlet surfing lokal, pengurus organisasi surfing, pelaku UMKM, penyedia penyewaan perlengkapan outdoor, dan pemilik vila di sekitar Pantai Senggigi. Data dianalisis secara deskriptif menggunakan persentase. Hasil penelitian menunjukkan bahwa aksesibilitas menuju lokasi (80%) dan keberadaan UMKM lokal (70%) merupakan faktor pendukung terkuat dalam pengembangan sport tourism berbasis surfing. Sementara itu, pengelolaan infrastruktur wisata (60%) dan ketersediaan pelatihan surfing (55%) berada pada kategori sedang, sedangkan kerja sama dengan pemerintah (45%) menjadi aspek yang paling lemah. Temuan ini menunjukkan bahwa Pantai Senggigi memiliki peluang yang baik untuk memperkuat surfing sebagai produk sport tourism, tetapi masih diperlukan perbaikan tata kelola, fasilitas pendukung, dan kolaborasi antar-pemangku kepentingan agar pengembangannya lebih berkelanjutan.